DIGITALISASI BERBASIS MASYARAKAT DI DESA TEBING DAN DESA TUIK SERTA WARGA BELAJAR PKBM BINA BANGSA KABUPATEN BANGKA BARAT, BANGKA BELITUNG - Utami, Atikah Dewi; Gustin, Gustin; Amrullah, Amrullah; Irawan, Dody (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2024)
By providing digitalization knowledge and training to residents in Tebing Village, Tuik Village, and PKBM Bina Bangsa Learning Residents, it is hoped that they will be able to overcome obstacles and problems in the village development process. The method used is PAR (Participatory Action Research), its implementation is carried out by analyzing several stages, namely preparation, implementation and evaluation. The results of the implementation of this activity showed that before the implementation of the activity, residents in Tebing Village, Tuik Village and PKBM Bina Bangsa Learning Community did not understand digitalization. However, after the implementation of the activity carried out by residents showed the increasing knowledge and competence in computer operation, especially as proven through post-test results. It is hoped that this research can provide information as a basis for consideration, support, and contribution of thought to decision makers in increasing digital-based competencies in order to improve public services to the community.